Applying ecosystem accounting to develop a risk register for peatlands and inform restoration targets at catchment scale: a case study from the European region - Stout, Jane; Farrell, Catherine (My University, 2022)
Combining natural capital accounting tools and ecosystem restoration approaches builds on existing frameworks to track changes in ecosystem stocks and flows of services and benefits as a result of restoration. This approach highlights policy-relevant benefits that arise due to restoration efforts and helps to maximize opportunities for return on investment. Aligning the System of Envi- ronmental Economic Accounting–Ecosystem Accounting (SEEA EA) framework with risk assessment tools, we developed a risk register for peatlands in two contrasting catchments in Ireland, based on available information relating to peatland stocks (extent and condition) and flows (services and benefits), as well as knowledge of pressures. This approach allowed for identification of areas to target peatland restoration, by highlighting the potential to reduce and reverse negative trends in relation to provisioning, regulating, and cultural services, flows relating to non-use values, as well as abiotic flows. We also highlighted ways to reduce and reverse the effects of historical and ongoing pressures through restoration measures, aligning our approach with that outlined in the SER International Principles and Standards for the Practice of Ecological Restoration. Building on the synergies between the SEEA EA and the SER Standards is highlighted as a means to develop transdisciplinary collaboration, to assist in setting and achieving targets set out under the UN Decade on Ecosystem Restoration as well as integrating regional policy targets set under the EU Biodiversity Strategy for 2030, and the related EU Habitats and EU Water Framework Directives.
PUBLISHED
cited By 0
Keywords: ecosystem; natural capital accounting tools; peatland stocks; ecosystem; natural capital accounting tools; peatland stocks